Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174040
|View full text |Cite
|
Sign up to set email alerts
|

You Watch, You Give, and You Engage

Abstract: Despite gaining traction in North America, live streaming has not reached the popularity it has in China, where livestreaming has a tremendous impact on the social behaviors of users. To better understand this socio-technological phenomenon, we conducted a mixed methods study of live streaming practices in China. We present the results of an online survey of 527 live streaming users, focusing on their broadcasting or viewing practices and the experiences they find most engaging. We also interviewed 14 active u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(105 citation statements)
references
References 32 publications
0
58
0
1
Order By: Relevance
“…In terms of live streaming behaviors, Zhou (2017) explored the associations among users' demographics, usage, and perceptions of live streaming. Lu et al (2018) investigated how content influences viewing behavior and engagement in Chinese live streaming.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of live streaming behaviors, Zhou (2017) explored the associations among users' demographics, usage, and perceptions of live streaming. Lu et al (2018) investigated how content influences viewing behavior and engagement in Chinese live streaming.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Recently, research investigated what drives people to tip and found that social interaction plays an important role (Deng and Chau, 2019;Lee et al, 2019). Lu et al (2018) interviewed users and suggested that tipping facilitates users to present and express themselves. Tipping also helps viewers win attention and admiration from other viewers.…”
Section: Motivations and Live Streaming Usementioning
confidence: 99%
See 1 more Smart Citation
“…Viewers typically react to the content, streamers, and one other though text-based communication channels, however an emerging trend in live streaming shifts emphasis of the medium from spectatorship to social interactions between streamers and their viewers [50]. For instance, viewers can respond to content, streamers, and one another via a text chat, emojis, and gifts [51,81].…”
Section: Live-streaming Platformsmentioning
confidence: 99%
“…This includes infuencing-in game challenges [66,77], placing bets [60], giving hits [48], and even controlling gameplay [45,47,62]. In spite of the benefts of rich audience participation dynamics, many live streaming platforms primarily support classic participatory mechanics, such as commenting via a text chat, emoting with icons, and gifting money [35,51,81,84]. One reason for this is that game live-streaming presently lacks an explicit representation of the design space in game live streaming.…”
mentioning
confidence: 99%